Advanced reservoir management and engineering - Ahmed, Tarek H., 1946- (Gulf Professional Pub., 2012)
One of the only books to cover management and engineering issues, this book offers readers a complete guide for formulating workflow solutions on a day-to-day basis. Authoritative in its approach, the book begins with the theory and practice of transient flow analysis and offers a brief but thorough hands-on guide to gas and oil well testing. Chapter two documents water influx models and their practical applications in conducting comprehensive field studies, widely used throughout the industry. Essential topics such as Type-Curve Analysis, unconventional gas reservoirs, and gas hydrates are also covered. The book moves on to provide a clear exposition of key economic and financial management methods for evaluation criteria and cash flow analysis, analysis of fixed capital investments and advanced evaluation approaches. This is followed by a frank discussion of advanced evaluation approaches such as integration of decision analysis and professional ethics. This edition includes three new management chapters, representing a 30% increase over the previous edition.